STAROSNA STRUKTURA VRHUNSKIH RVAČICA - Goran Kasum; Mališa Radović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
It's pretty clear that todays wrestlers must possess comprehensive general and special preparation, rich technical-tactful repertoire, sport's intelligence, strong nerv system, good motivation and emphasized readiness to carry all training and competitive temptations. These general assumptions were analyzed by many specialists through many different aspects. Some of them emphasized technical preparation as the main factor and others underlined tactful qualifi cation. The most of specialists emphasized the unbreakable unity and connection of technical, tactful, physical and psychological preparation of top wrestlers. Although there are some disagreements about the way of preparation, all specialists agree that good selection of candidates is necessary for the top results. Candidate's age and his fi ttnes in age characteristics specifi cal for certain category are one of the main criterion for selection. It's not rare coaches give up the most qualifi ed competitor at that moment with the reason that the competitor won't be able to be a candidate for the highest standing at the time of Olimpics. In this essey, special attention is commited to the analyze of age-structure of womens wrestlers with the special Athens Olimpics 2004. review